Clinical study of the treatment of digital exostosis by introducing a biocompatible gel - Giralt de Veciana, Enrique; de Planell Mas, Elena; Bonill a Toyos, Elvira Mª; Novel Martí, Virginia; Truchero Coma, Consuelo; Manzanares Céspedes, Mª Cristina (Revista Internacional de Ciencias Podológicas, 2012)
Precedents. Digital exostosis is a common pathology often seen in podiatry clinics. Despite the high rates of incidence, it is a rarely studied clinical entity. Currently proposed treatments are: conservative treatment with silicone orthosis, and surgical treatment based on the resection of exostosis. We consider that an alternative treatment is necessary. Polyacrylamide Gel (PAAG) injection would bring patients more benefits and less drawbacks than the available treatments. Materials and Methods. The clinical study was conducted between October 2006 and February 2009, with 54 patients (2 male and 52 female) aged between 43 and 85 years, affected by digital exostosis. Injection of biocompatible gel is performed in the area of exostosis, to isolate it and avoid pressures according to the described injection technique. All patients signed the informed consent. Data was recorded objectively and subjectively for each of the patients. Subsequent evaluation and statistical treatment of data were carried out separately and anonymously. Statistical software SPSS-PC 17.0 was used for the statistical analysis of data. Results. Interdigital heloma located in the fourth interdigital space and in the fifth toe appeared in 35,2% of cases; heloma on the back of middle toe in 11,1% of cases; interdigital heloma in the fourth interdigital space and in the fourth toe in 9,3% of cases, and the remaining primary lesions in 14,9% of the total cases. For each case, several items were observed: previous treatments, quantity of injected gel, reaction to injection, controls, and patient’s satisfaction after treatment. 57,4% of patients had not undergone any previous treatment, whereas 33,3% of patients had already used a silicone orthosis. After analysing the quantity of injected PAAG in each case, it was obtained an average of 0,542 cc with a typical deviation of 0,2237cc. Minimum injected quantity was 0,20 cc, while the maximum quantity injected was 1,50 cc. Reaction was observed 24 / 48 hours after injection, and it was almost the same as in the initial period. Four post-injection controls were carried out one week after injection, one month after, three months after, and six months after injection. After six months, we could conclude that in the majority of cases –45 out of 54– the initial PAAG lump at injection site persisted. Patient satisfaction was evaluated 1 week after injection, one month after injection, three months after, and six months after. After 6 months, the rating of patient satisfaction was 98%. Conclusions. The treatment of heloma caused by digital exostosis by injection of polyacrylamide gel, using a technique established in the protocol of this study, is considered feasible, to be reproduced, and effective. The product has achieved high rates of tolerance and adaptation to the anatomic structures, diminishing side effects, proving it is a safe method to obtain top results related to effectiveness of treatment and pain lessening. We can conclude that polyacrylamide gel injection has become a new option for the treatment of digital exostoses.
Keywords: Digital Exostosis; Polyacrylamide Gel; Injection; Heloma.